Process Incentives by the Intensification of a Conventional Biodiesel Plant. (2016) - Narasimhan, V.; Mani, Samuel; Varghese, Jomy; Manilal, A.M.; Fasnabi, P.A.
Abstract: With the exponential growth of global energy demand and the rising prices of conventional fuels, the necessity of developing proper alternative fuels is at an all-time high. Biodiesel is considered to be a suitable alternative that has the potential to reduce the amount of future fossil fuel requirement substantially. Process intensification is the method of combining several unit processes or operations to a single unit. The scope of the paper includes comparison of the conventional and intensified biodiesel plants through simulation in Aspen Plus V. 8.6 and subsequent result analysis. The conversion and hot utility requirement of the conventional and intensified biodiesel plants are compared and the reasons for the same are discussed. The reactive distillation process is found to have a higher conversion and lower hot utility requirement.